Knowledge Management Components and Their Impact on Work Engagement of Employees - Rožman, Maja; Shmeleva, Zhanna; Tominc, Polona (Naše gospodarstvo/Our economy, 2022)
In light of globalization and modern business, companies are typically exposed to challenges caused by unpredictable and complex competitive environments. The business environment, with global trends and stringent competition in the world market, now faces significant changes that companies should introduce into their current business operations. Among them, the human resource management of knowledge employees has become extremely important. The main aim of this article is to establish the impact of components of knowledge management on work engagement of employees in Slovenian companies. In the empirical part of the research, a sample of 112 Slovenian companies was obtained. Senior managers of companies and their employees were surveyed, using the questionnaire developed based on existing measurement scales. The results will help us to better understand the importance of knowledge management in Slovenian companies and its importance as a business strategy that must be fully integrated within all of the employees’ related processes of the company.